Data in support of a functional analysis of splicing mutations in the IDS gene and the use of antisense oligonucleotides to exploit an alternative therapy for MPS II - Matos, Liliana (Data Brief, 2015)
This data article contains insights into the methodology used for the analysis of three exonic mutations altering the splicing of the IDS gene: c.241C>T, c.257C>T and c.1122C>T. We have performed splicing assays for the wild-type and mutant minigenes corresponding to these substitutions. In addition, bioinformatic predictions of splicing regulatory sequence elements as well as RNA interference and overexpression experiments were conducted. The interpretation of these data and further extensive experiments into the analysis of these three mutations and also into the methodology applied to correct one of them can be found in “Functional analysis of splicing mutations in the IDS gene and the use of antisense oligonucleotides to exploit an alternative therapy for MPS II” Matos et al. (2015) [1].